Peningkatan Kemampuan Menulis Puisi dengan Media Gambar Peristiwa pada Siswa Kelas VIII SMP Negeri 26 Bandar Lampung Tahun Pelajaran 2020/2021 - Wahono, Wahono (Lentera: Jurnal Ilmiah Kependidikan, 2023)
This study aims to describe the use of event image media as an improvement in the ability to write poetry. This class action research consists of three stages, namely the precyclical stage, the si- klus I, and cycle II. Each cycle consists of planning, execution, observation, and reflection. The subject of this study was a class VIII student of SMP Negeri 26 Bandar Lampung for the 2020/2021 academic year. In data collection used test and nontest techniques In the collection of data used test and nontest techniques. The test technique is in the form of the results of writing student poems, while the non-test technique is in the form of field notes, observations, interviews, questionnaire sheets, and photo documentation. The data analysis techniques used are qualitative and quantitative techniques. Data presentation is carried out by informal techniques. Based on the results of the data analysis that has been stated, it can be implied that the use of event image media as an increase in the ability to write poetry in grade VIII students of SMP Negeri 26 Bandar Lampung for the 2020/2021 academic year consists of cycle I and cycle II. In precyclical, students write poems without using media. On cycle I and cycle II students write poems using the medium of images of events that have been prepared and determined by the researcher.